Residuos derivados de madera como alternativa de sustrato para almacigo y producción de plantines de Begonia Nonstop (Begonia x Tuberhydrida) bajo condiciones controladas - Morocco Arapa, Romel Wilson (2025)
ABSTRACT This research aimed to determine how the use of different wood-based seedling substrates influences the production of Nonstop begonia (Begonia x tuberhybrida var. Nonstop) seedlings. The experiment was conducted in the greenhouse facilities of the Gardening and Green Areas Subunit of the National University of San Agustín from April to July 2024. The objective was to explore the use of alternative substrates based on wood derivatives for begonia seedling production. The substrates studied were: lupuna and pashigua sawdust + 10% perlite + 10% vermiculite, 40% peat + 40% crushed biochar + 10% perlite + 10% vermiculite, cardboard fiber + 10% perlite + 10% vermiculite, palm fiber + 10% perlite + 10% vermiculite, and a commercial substrate (peat + vermiculite and perlite) as a control. Using a completely randomized design (CRD), five different treatments were compared. Each treatment was replicated four times, resulting in 20 experimental units. In each unit, 98 begonia seedlings were grown, providing a total sample of 1960 seedlings for the study. A comparative analysis of the evaluated treatments showed that substrate T4 (palm fiber + 10% vermiculite + 10% perlite) provided the optimal conditions for the development of Nonstop begonia seedlings, outperforming the control treatment T0 (peat + vermiculite + perlite). Plants grown in this substrate exhibited superior commercial characteristics, such as a higher number of leaves, uniform height, shorter germination and transplanting time, and a high germination percentage. The physical and chemical properties of substrate T4 (porosity, density, pH, electrical conductivity) were optimal for plant development. These results demonstrate the potential of palm fiber as a viable and sustainable substitute for traditional substrates in ornamental plant production. Keywords: Substrate, wood derivatives, begonia